Entropy, Search, Complexity - Csiszár, Imre; Katona, Gyula O.H; Tardos, Gabor (Bolyai Society Mathematical Studies, 2007)
The present volume is a collection of survey papers in the fields of entropy, search and complexity. They summarize the latest developments in their respective areas. More than half of the papers belong to search theory which lies on the borderline of mathematics and computer science, information theory and combinatorics, respectively. Search theory has variegated applications, among others in bioinformatics. Some of these papers also have links to linear statistics and communicational complexity. Further works survey the fundamentals of information theory and quantum source coding. The volume is recommended to experienced researchers as well as young scientists and students both in mathematics and computer science.